Impact of derivatives trading on spot markets: price discovery - Kamau, Kelvin Gacheru (Strathmore University, 2017)
A derivative security is a financial contract whose value is derived from the value of something else, such as stock price, a commodity price, an exchange rate, an interest rate, or even an index of prices, (Sakar, 2006). Derivatives may be traded for a variety of reasons; a derivative enables a trader to hedge some preexisting risk by taking positions in derivatives markets that offset potential losses in the underlying or spot markets. Speculation, taking positions to profit from anticipated price movements, is also a major motive for derivatives trading. In practice, active markets require the participation of both hedgers (they participate in the markets to manage their spot market price risk) and speculators who speculate on the direction of the futures prices with the intention of making profits, since it may be difficult to distinguish whether a particular trade is for hedging or speculation purposes. Arbitrage trading which entails profiting from discrepancies in the relationship of spot and derivatives prices, helps to keep markets efficient and may also act as a motive for derivatives trading. Speculators face the risk of losing money form their derivatives trades depending on the price volatility in the markets.
A Research project submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Actuarial Science at Strathmore University
Keywords: Market stabilization; Derivatives trading; Capital markets